2017
DOI: 10.1016/j.marstruc.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modelling of cross-flow vortex-induced vibrations

Abstract: Semi-empirical models are commonly used to predict vortex-induced vibrations (VIV). Empirical parameters are often based on forced harmonic motion tests of short rigid cylinders in one degree of freedom, which is a significant simplification of the three dimensional VIV experienced by flexible cylinders. Still, the models may provide satisfactory estimates of the response of slender marine structures exposed to current. At least in terms of root mean square (r.m.s.) of displacements and strains, dominating fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They showed that the low-order riser modes are very sensitive to the measurement noise. Recently, a stochastic modelling of cross-flow VIV in time domain has been presented by Ulveseter et al (2017) who introduced a Gaussian random process through a synchronization between vortex shedding and cylinder frequencies. They predicted a chaotic VIV response depending on the specified empirical coefficients and the assumed random process spectrum.…”
Section: Literature Related To Uncertainty In Viv Modellingmentioning
confidence: 99%
“…They showed that the low-order riser modes are very sensitive to the measurement noise. Recently, a stochastic modelling of cross-flow VIV in time domain has been presented by Ulveseter et al (2017) who introduced a Gaussian random process through a synchronization between vortex shedding and cylinder frequencies. They predicted a chaotic VIV response depending on the specified empirical coefficients and the assumed random process spectrum.…”
Section: Literature Related To Uncertainty In Viv Modellingmentioning
confidence: 99%
“…Monte Carlo simulations are the simplest way to tackle non deterministic problems since the solution just requires the generation of synthetic realizations of the turbulent flow and the statistical analysis of the response (Tagliaferri and Srinil, 2017). This approach has also been used to determine the response of structures with many more degrees-of-freedom (Li, 2019) or in more complicated geometries than the 2-D case of simple wake-oscillator models (Ulveseter et al, 2017). Although being simple to implement, the Monte Carlo approach does not offer the same depth of understanding as explicit closed form solutions which are only valid in some simple configurations, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…J.V. Ulveseter et al [33] mentioned that the equation of motion was solved by the time integration scheme Newmark-β method. According to Ref.…”
Section: Introductionmentioning
confidence: 99%